The issues of interpretation of “health”, “pain” and “suffering” concepts in modern multidisciplinary science - Diorditsa, Ihor; Katerynchuk, Kateryna; Kyrenko, Sergiy; Vasylkivska, Iryna; Bespal, Olha (Linguistics and Culture Review, 2021)
The research given is of great scientific value since the main task of any state is to protect natural human values, namely: life, health, will, honour, dignity, and other natural rights. Therefore, their defence and protection are carried out at the state level, especially by developing effective means aimed at systematic counteraction to criminal offences against the health of an individual. The doctrinal approaches on the limits of criminal law protection of person’s health, existing today, require a detailed analysis and generalization, as well as legal drawbacks in the construction of criminal law norms on liability for various types of encroachments on health and problems arising as a result of it at criminal law assessment of relevant socially dangerous acts. However, the discussion on terminology which is not only the achievement of criminal law subjects but also medicine, forensic medicine, psychology, etc., is still taking place between the researchers in various humanitarian sciences at national and international levels. First of all, these terms and categories are the determinants, and main studies in these areas are based on them.